Screening for Fabry Disease in Kidney Disease: a Cross-Sectional Study in Males and Females - Luciana Senra de Souza Sodré; Rosália Maria Nunes Henriques Huaira; Marcus Gomes Bastos; Fernando Antônio Basile Colugnati; Marcelo Paula Coutinho; Natália Maria da Silva Fernandes (Karger Publishers, 2017)
Background/Aims: Evaluate the prevalence of Fabry disease in men and women with kidney disease; and observe the presence and importance of the main signs and symptoms in patients with kidney disease. Methods: A cross-sectional analysis of secondary data from a multicenter project of Clinical and Epidemiological Analysis of Fabry Disease in 854 Dialysis Centers. A total of 36,442 patients underwent the questionnaire and algorithm; of them, 28,284 were discarded for not presenting signs and symptoms of Fabry disease, while the other 8,087 submitted to blood collection and analysis. All participants signed a Free and Informed Consent Form and a questionnaire was applied. The questionnaire data were analyzed using a computerized algorithm. This program/algorithm analyzes and separates patients into: discarded, patients unlikely to have Fabry disease; suspect, patients who submitted to blood collection. The blood of suspect patients was collected on filter paper for enzyme measurement and genetic testing. A descriptive data analysis was performed and the likelihood ratio was determined. Results: The general prevalence was 0.19% and after use of algorithm was 0.87%. Although more men were screened (59.3%), the prevalence was higher in women (65.1%). The most prevalent signs and symptoms were: heart disease (60.6%), decreased or lack of sweating (42.3%), heat and cold intolerance (28.2%), and pain crises spreading throughout the body (26.8%). Conclusion: The prevalence was higher in women, and the most prevalent symptom was heart diseases.